THE NEED TO ATTRACT FOREIGN INVESTMENTS TO THE NATIONAL ECONOMY ON A LARGE SCALE - Umirova Gulmira (Academia Science Repository, 2023)
Today, investments, including foreign investments, are very important in the social, economic and political development of the country. It is known that any country cannot develop without learning world experiences, without accepting the achievements of the world's leading countries in the field of science, science and technology.